2006
DOI: 10.1037/0090-5550.51.3.190
|View full text |Cite
|
Sign up to set email alerts
|

A stress process model of caregiving for individuals with traumatic brain injury.

Abstract: Objective: To test a stress process model of caregiving for persons with traumatic brain injury. Design: A correlational study using path analysis. Participants: One hundred eight caregivers affiliated with community-or Web-based support groups. Main Outcome Measures: The Modified Caregiver Appraisal Scale, the World Health Organization Quality of Life-Brief Version, the Interpersonal Support Evaluation List, and the COPE. Results: The normed fit index, comparative fit index, and parsimony ratio indicated a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 74 publications
8
68
1
1
Order By: Relevance
“…Some caregiver studies demonstrate that a passive coping style is maladaptive, but find no effect of an active coping style on psychosocial functioning [37,39,40]. Other studies on the chronic phase after sustaining an injury or illness related the use of active coping to maladaptive outcomes [29,38,41,42]. In order to interpret these diverse findings, we assume that it is important first to determine whether the stressful situation is controllable or uncontrollable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some caregiver studies demonstrate that a passive coping style is maladaptive, but find no effect of an active coping style on psychosocial functioning [37,39,40]. Other studies on the chronic phase after sustaining an injury or illness related the use of active coping to maladaptive outcomes [29,38,41,42]. In order to interpret these diverse findings, we assume that it is important first to determine whether the stressful situation is controllable or uncontrollable.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we only measured passive coping style as an example of emotion-focused coping styles; it might also be the case that other forms of emotionfocused styles, such as avoidance or seeking social support, increased. Changes in coping styles might be influenced by, among others, the amount of support from family and friends, social or emotional problems existing before the stroke and personality factors, such as neuroticism, pessimism and locus of control [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the way patients cope with the negative effects of the trauma and with problems in everyday life has a major influence on the adaptation process (Anson & Ponsford, 2006a;Chronister & Chan, 2006;Finset & Andersson, 2000). Coping refers to "the person's cognitive and behavioural efforts to manage (reduce, minimise, master, or tolerate) the internal and external demands of the person-environment transaction that is appraised as taxing or exceeding the person's resources" (Folkman, Lazarus, Gruen, & DeLongis, 1986, p. 572).…”
mentioning
confidence: 98%
“…Outcomes are the variables under investigation which can be influenced by stressors; they can include a myriad of health, mental health and social conditions, ranging from heart problems, to anxiety, to social dilemmas at work. Pearlin (1989) Numerous relationships between life events and strains and potential outcomes have been studied using the stress process as a theoretical model, including spanking and child depressive symptoms (Christie-Mizell et al 2008), caregiving and quality of life (Chronister and Chan 2006), racial discrimination and psychological distress (Ong et al 2009), and school climate and teacher burnout (Grayson and Alvarez 2008). In each study, researchers captured a particular stressor and outcome of interest, then used the stress process model to investigate the relationship between the two and any potential moderating factors.…”
Section: Chapter 2 -Literature Review the Stress Processmentioning
confidence: 99%